Towards the third dimension in direct electron beam writing of silver - Höflich, Katja; Jurczyk, Jakub Mateusz; Madajska, Katarzyna; Götz, Maximilian; Berger, Luisa; Guerra-Nuñez, Carlos; Haverkamp, Caspar; Szymanska, Iwona; Utke, Ivo (Beilstein Journal of Nanotechnology, 2018)
Carboxylates constitute an extremely promising class of precursor compounds for the electron beam induced deposition of silver. In this work both silver 2,2-dimethylbutyrate and silver pentafluoropropionate were investigated with respect to their dwell-time-dependent deposition behavior and growth characteristics. While silver 2,2-dimethylbutyrate showed a strong depletion in the center of the impinging electron beam profile hindering any vertical growth, silver pentafluoropropionate indicated a pronounced dependency of the deposit height on the dwell time. Truly three-dimensional silver structures could be realized with silver pentafluoropropionate. The pillars were polycrystalline with silver contents of more than 50 atom % and exhibit strong Raman enhancement. This constitutes a promising route towards the direct electron beam writing of three-dimensional plasmonic device parts from the gas phase.
Keywords: carboxylate; electron beam induced deposition; silver; three-dimensional nanostructures; vertical growth rate